Whetstones in Roman Britain: Character, Distribution, Provenance and Industries. (November 2022) - Allen, J.R.L.
Abstract: A substantial database of published excavation and other reports has been used to map the character and distribution in Roman Britain of whetstones, those unprepossessing implements essential in the home, farmstead, workshop and barracks for the maintenance of edge-tools and weapons. The quality of the geological identifications in the reports varies considerably, but a wide range of lithologies are reported as put to use: granite, basalts-dolerites, lava, tuff, mica-schist, slates/phyllites, Brownstones, Pennant sandstone, micaceous sandstones, grey sandstones/siltstones, Millstone Grit, Coal Measures, red sandstones, ferruginous sandstones, sarsen, Weald Clay Formation sandstones, sandy limestones, shelly limestones, cementstones, and (Lower) Carboniferous Limestone. On distributional evidence, some of these categories are aliases for alternatively and more familiarly named lithologies. Bringing 'high-end' products to the market, the long-running industry based on sandstones from the Weald Clay Formation (Lower Cretaceous) emerges as a British economic feature, evidenced from the Channel coast to the Scottish Borders, and with a recently demonstrated, substantial representation on the Roman near-continent. The distribution maps point to another and more complete British industry, based on the Brownstones (Old Red Sandstone, Devonian) and Pennant sandstone (Upper Carboniferous), outcropping close together in the West Country. A more systematic and geology-based treatment of excavated whetstones in the future is likely to yield yet more insights into the role these artefacts played in the economy of Roman Britain.